Corn Cob Jam Stick / Nor Imanina Yunus ... [et al.] - Yunus, Nor Imanina; Yahaya, Nur Syahirah; Darmadi, Fatimah Zahrah; Supian, Intan Nur Ridhwa; Ayub, Nurhanini (2023)
Our company, Gerbang Enterprise, has clear objectives in producing our new product, It’s Corn!, which is to utilise surplus from corn product as a value-added product, to create a new flavour in other jam lines in the market and also to improve the packaging of existing jam product offers the consumers the experience of enjoying jam in a stick packaging. It is based on the idea of the yield of corn cob waste in the food industry, since many food manufacturers use corn to make ready-to-eat (RTE) and instant-cook (RTC) corn products, among other things. Gerbang decided to make jam from corn cobs so that all of the corn harvest could be used. It's Corn! is primarily made up of corn cobs collected from the food industry or another sector that discards corn cobs. The corn cob-boiling water will be combined with sugar and gelatine and then packaged. Despite the fact that some households have already made corn cob jam at home, the process of preparing a certain quantity of jam requires some effort. Thus, It's Corn! is designed to produce an RTE product that customers can easily purchase and consume. It's Corn!, can be consumed by individuals of all ages, including seniors, adults, and children, because it is not overly sweet and has a honey-like flavour. The target customer is primarily people who are working individuals and have no time to cook their own meal, travellers and backpackers hence, a ready-to-eat food product such as corn cob jam is needed for them. Vegans could also be the target market; in which case the honey-like taste jam product could be an option or preference for vegans who attempt to minimise or avoid the intake of honey because it is a form of animal exploitation. In terms of competitors in the market, we faced many challenges, yet we still persist in continuing and developing our business. Some notable competitors in the market are Choki Choki, Smucker’s Fruit Jam and Shuib Honeybeestix Factory. In this report we analyse all competitors’ strengths and weaknesses. We have the advantage at the packaging since we are the first company in Malaysia to produce jam product in stick packaging, unlike Smucker’s Fruit Jam which is sold in jar packaging. We are also vegan friendly; therefore, our market is bigger since both nonvegan and vegan can consume our product. Other than that, we might as well be a good option for nutritious product compared to Choki Choki which is selling chocolate paste with high sugar content.